Nutritional Studies and Antioxidant Profile of Pickled Oyster Mushrooms of North East India - Deb, Utsab; Anilakumar, K R; ., Mallesha; Chatterjee, Soumya (Defence Life Science Journal, 2017)
Mushroom is a very popular food that is consumed around the globe yet it finds very limited acceptance in India, that too mainly among the elite. Non-availability of mushrooms around the year and its highly perishable nature makes it an expensive commodity for the common people to afford. Hence pickling may be viewed as a method to increase the shelf life of oyster mushrooms from 4-7 days under refrigerated condition to at least up to 12 months at room temperature. Hence a recipe for pickling of mushrooms using Indian spices was formulated so as to suit the Indian palate. The proximate analysis, calorific value, mineral and fatty acid profile along with antioxidant profile of the mushroom pickle was elucidated. Sensory parameters and shelf life and stability determining data like pH, titratable acidity and microbiological profile of the pickle was also performed. Finally it was observed that the mushroom pickle formulation has a shelf life of at least 12 months at room temperature with an overall acceptability (OAA) score above ‘very good’ mark.